Role of endothelin receptor type B (EDNRB) in lung adenocarcinoma - Wei, Feiran (Thorac Cancer, 2020)
BACKGROUND: The five‐year survival rate of lung adenocarcinoma patients (LUAD) is very low,and the methods of predicting survival are a great obstacle for LUAD therapies. Endothelin receptor type B (EDNRB) gene is associated with tumorigenesis. In this study, we aimed to evaluate the predictive value of EDNRB on LUAD. METHODS: Survival analyses was performed to assess the correlation between EDNRB expression and survival of LUAD patients from the Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) datasets. Gene set enrichment analysis (GSEA) was conducted to illustrate possible biological functions of EDNRB. Laboratory methods were used to verify the function of EDNRB in LUAD. RESULTS: The TCGA results showed that a low expression of EDNRB was found in LUAD patients which led to poor outcome and worse survival, compared with the high expression in GSEA results which suggested that expression of EDNRB might be associated with regulation of the ERK pathway. Laboratory results suggested that EDNRB could inhibit the proliferation and migration of LUAD H1299 cells. CONCLUSIONS: EDNRB is a potential prognostic marker for LUAD patients and might exert its functions by regulating the ERK pathway in LUAD.